Cloning and expression of fungal alpha-amylase genes in Saccharomyces cerevisiae with integrated glucoamylase gene for raw starch conversion into bioethanol - Sakwa, Liana-Lisa (Stellenbosch : Stellenbosch University, 2017)
Thesis (MSc)--Stellenbosch University, 2017.